Cyber-Village a community for software development - Li, August K. (College of Architecture, University of the Philippines, Diliman, 2000)
Studies impact of emerging technologies (e-commerce, online-communities) on the planning of the software development community. This study develops guidelines for the design of an software development community. A well-designed software development community can enhance creativity and productivity, attract more locators and be a catalyst in transforming Philippines into a knowledge center in Asia.